Hybrid UV/MLFMA Analysis of Scattering by PEC Targets above a Lossy Half-Space - Li, Mengmeng; Chen, Hua; Li, Chunyan; Chen, Rushan; Ong, Chong-Jing (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An efficient hybrid UV method and the multilevel fast multipole algorithm (MLFMA) is proposed for the analysis of scattering by arbitrary three-dimensional(3-D) perfect electric conductor (PEC) targets above a lossy half-space. The proposed method modifies the MLFMA based on the real-image representation of the half-space dyadic Green’s function. Unlike the original MLFMA, the interaction matrix of the UV/MLFMA is split into the “near” terms, the “intermediate” terms, and the “far” terms. The “near” terms are handled via the method of moments (MoM), the “intermediate” terms are handled via the UV method, and the “far” terms are handled via the MLFMA. The error arising from the approximation to the half-space dyadic Green’s function via the real-image representation in the “intermediate” terms can be avoided by using the UV matrix compression. The memory requirement and computational time of the “near” terms are also decreased significantly compared with the original MLFMA.